Content Analysis of the Sixth Scientific Grade Mathematics Textbook According to Mathematical Content Domains (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The present research aimed to:• Identify the mathematical content domains that should be included in the Sixth Scientific Grade mathematics textbook.• Determine the extent to which these domains are covered in the textbook.To achieve these objectives, the researcher developed a list of mathematical content domains after reviewing relevant literature, studies, and previous research on mathematical knowledge and its components. An initial draft of the list was prepared, and its validity was verified through consultation with a panel of experts. The final version comprised four main components: concepts, principles and generalizations, skills, and problem solving. The researcher then analyzed the Sixth Scientific Grade mathematics textbook for the academic year 2024–2025. A total of 247 pages were examined, excluding introductory sections, questions, and indices. The analysis was conducted based on explicit ideas, with results recorded using frequencies and percentages, applying the descriptive method through content analysis. Reliability of the analysis was ensured through agreement between the researcher, external reviewers, and intra-rater consistency over time, using Cooper’s formula as a statistical measure. Data were processed using the SPSS statistical package, employing measures such as percentages and Cooper’s formula. The findings revealed that:• The Sixth Scientific Grade mathematics textbook demonstrates a strong applied orientation, with a high emphasis on problem-solving compared to theoretical concepts.Based on these findings, the researcher proposed several recommendations and suggestions, as presented at the end of Chapter Four.